Regulasi Hukum Terhadap Pemidanaan Orang Yang Melakukan Kohabitasi (Kumpul Kebo) - Sholikah, Ana; Hidayati, Rahmatul; Parmono, Budi; Muhibbin, Muh; Ilmania, Nurika Falah (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Cohabitation (cohabitation) is an act that violates the juridical and social norms of criminal law carried out in the State of Indonesia. The research was prepared to find out the legal rules for cohabitation offenders and a comparison of cohabitation according to the Criminal Code Law Number 1 of 1946, Law Number 1 of 1951 and Emergency Law Number 1 of 1951 concerning Temporary Measures to Organize the Unity of the Structure of Powers and Procedures of Civil Courts. This research is normative juridical research using the technique of approaching the law. The results of the study reveal that in the regulation there is no explicit formulation policy on cohabitation in the Criminal Code / WvS. Legal arrangements for cohabitation offenders are contained in Article 412 of Law Number 1 of 2023 but have not been enforced. So that the legal arrangements for cohabitation offenders use Jurisprudence, but only certain regions use it. Keywords: Regulation; Legal Consequences; Cohabitation.